Pansitopenia as a Marker of Advanced Human Immunodeficiency Virus (HIV) infection: How Often? A Case Study Accompanied by Literature - Priyanto, Muhammad Hikmawan; Faizun, Muhammad (Indonesian Health Journal (IHJ), 2024)
Pansitopenia is a condition characterized by anemia, thrombocytopenia, and leukopenia. One of the common etiologies of Pansitopenia is HIV infection. In advanced HIV, Pansitopenia may present even without other clinical findings leading to a diagnosis of HIV. This study was conducted as a case study of a 34-year-old man who presented with chief complaints of chronic diarrhea and fever that lasted for one month. Laboratory examination showed Pansitopenia, HIV-rapid reactive and peripheral blood picture indicating Pansitopenia/ aplastic anemia. Data were collected through history taking, physical examination, and a series of laboratory tests. The patient was diagnosed with Pansitopenia suspected to be caused by HIV infection. The chief complaints of chronic diarrhea and fever suggested a chronic disease process due to immune compromise, as seen in the patient's clinical status indicating advanced HIV. The literature suggests that the severity of pansitopenia depends on the severity of HIV disease. Pansitopenia can be an indicator of the advanced stage of HIV infection. Appropriate management and regular monitoring are essential to prevent further complications. Pansitopenia in HIV patients can be considered as an important indicator to assess the severity of the infection. Prompt treatment and antiretroviral therapy are highly recommended to improve the prognosis of patients.